Plant design and operations - Sutton, Ian (GPP, 2015)
This book provides practical guidance on the design, operation, and maintenance of process facilities to managers, engineers, operators, and maintenance specialists. It is supported by useful, real-world examples and experience from a wide range of facilities and industries and includes guidance on occupational health and safety, industrial hygiene and personal protective equipment. Topics covered include: energy control; safety in design; security, equipment, and transportation. A logical, practical guide to maintenance task organization is provided, from conducting a job hazards analysis to the issue of a work permit, and to the shutdown and isolation of equipment. Common hazards are covered in detail, including flow problems, high pressure, corrosion, power failure, and many more. -- Edited summary from book.
Keywords: Chemical plants -- Design and construction.; elektronické knihy; electronic books